Numerical Study on Seismic Behavior of Underwater Bridge Columns Strengthened with Prestressed Precast Concrete Panels and Fiber-Reinforced Polymer Reinforcements - Yu Tang; Gang Wu; Zeyang Sun (International Journal of Polymer Science)
The seismic performance of the bridge column, such as pier or pile, is a time-dependent property which may decrease in resistance to the deterioration or natural hazards along the structure’s service life. The most effective strengthened method for degraded bridge columns is the jacketing method, which has been widely developed and investigated through numerous studies since the 1980s. This paper presented a modeling method, as well as a comprehensive parametric study, on seismic performance of bridge columns strengthened by a newly developed strengthening method with prestressed precast concrete panels and fiber-reinforced polymer reinforcements (PPCP-FRP). A modeling method of bridge columns strengthened with PPCP-FRP was first presented and validated with test results. The influence of design parameters, such as axial load ratio, equivalent FRP reinforcement ratio rate (EQFRR), expansion ratio, and shear span ratio of strengthened columns, were then further evaluated in terms of lateral load capacity, ductility, energy dissipation, lateral stiffness, and residual displacement of strengthened columns. The peak load of strengthened columns increases with the increasing of EQFRR due to the unique failure model of strengthened columns characterized by the fracture of FRP bars. The initial stiffness of strengthened columns increased by 300% with the increasing of expansion ratio by 45%, and a stable postyield stiffness stage was obtained by most strengthened columns in analysis. The residual displacement of strengthened columns decreases rapidly with the increasing of EQFRR, which indicated that a better repairability could be achieved by the strengthened column with a relatively high EQFRR.